The structure of Adonis wolgensis Stev. coenopopulation in the conditions of Northern Kazakhstan - Sultangazina, G.J.; Kuprijanov, А.N.; Kuprijanov, О.А.; Steshenko, M.Y. (Fundamental and Experimental Biology, 2020)
The article presents the study results made on the Adonis wolgensiscoenopopulation in Northern Kazakhstan (2018–2019). The materials have been gathered in the course of field research taking into account the literary data. The age structure of the coenopopulations is provided on the basis of detailed route studies. There have been studied eight coenopopulations located in Akmola, Pavlodar, and Kostanay regions. A. wolgensisis a short-stem herbaceous polycarpic of Northern Kazakhstan. A. wolgensiscoenopopulations are found in three main habitats: steppe, meadow-steppe, and forest communities. The study of A. wolgensis coenopopulations in the latitudinal direction from Ekibastuz in the east to the Kostanay region in the west has revealed a high recovery index in steppe ecotopes. In other coenopopulations it is less than one. It is especially low in forest habitats. Most coenopopulations have a normal character according to the spectrum of age conditions, and they are maturing. This fact proves no negative impact of environmental and anthropogenic factors on the structure of coenopopulations and ensures their recovery and preservation.